2004
DOI: 10.1007/s00464-003-9082-0
|View full text |Cite
|
Sign up to set email alerts
|

Videobronchoscopic guidance makes percutaneous dilational tracheostomy safer

Abstract: The surgeon performing PDT guided by VB has a higher degree of safety, resulting in less bleeding than with PDT guided by CB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 20 publications
0
14
2
2
Order By: Relevance
“…[19] Since a majority of studies included in this review used the multiple dilator technique, it is not surprising to know that the results failed to demonstrate any particular benefit from one specific technique of PDT. While it has been suggested that the use of a bronchoscope to guide the operator performing the PDT makes the procedure safer,[20] this was not supported by the results of our analysis.…”
Section: Discussioncontrasting
confidence: 86%
“…[19] Since a majority of studies included in this review used the multiple dilator technique, it is not surprising to know that the results failed to demonstrate any particular benefit from one specific technique of PDT. While it has been suggested that the use of a bronchoscope to guide the operator performing the PDT makes the procedure safer,[20] this was not supported by the results of our analysis.…”
Section: Discussioncontrasting
confidence: 86%
“…Estimamos que estos momentos ciegos son los que explican las complicaciones, morbilidad y mortalidad asociadas a la técnica clásicamente descrita, pues al mantener un control endoluminal continuo, logramos disminuir complicaciones asociadas a errores de comunicación entre broncoscopísta que evalúa la vía aérea de forma autónoma y que comunica al operador de la TQT sobre si está o no bien posicionada la aguja y las cánulas de dilatación. Se ha demostrado que el uso de FBC disminuye riesgo de complicaciones durante TQT percutánea 12,13 , si bien existen pocos estudios que comparen distintas técnicas de FBC, estos muestran resultados positivos hacia la realización de TQT percutánea con asistencia por FBC 14,15 . La técnica de TQT percutánea "bed-side" se realiza en el 84,5% del total de TQT que se requieren en la unidad de cuidados intensivos por cualquier causa, siendo sólo el 15,5% realizadas por especialistas en otorrinolaringología, lo que adicionalmente es una fuente de ahorro de recursos importante para las instituciones de salud, puesto que este tiempo no es sólo de recurso médico especialista en falencia, sino también el ahorro en uso de tiempo de pabellones quirúr-gicos, insumos de pabellón y costo de oportunidad.…”
Section: Discussionunclassified
“…During percutaneous tracheostomy, bronchoscopy enables the direct visualisation of the anterior tracheal wall puncture, which may provide a higher degree of safety . A chest X‐ray may therefore be warranted in percutaneous tracheostomy performed without bronchoscopic guidance.…”
Section: Discussionmentioning
confidence: 99%